Vedolizumab in the treatment of inflammatory bowel disease: evolving paradigms - Benjamin Crooks; Tom Barnes; Jimmy K Limdi (BioExcel Publishing Ltd, 2020)
Inflammatory bowel diseases, comprising Crohn's disease (CD) and ulcerative colitis (UC), are chronic, relapsing and remitting immune-mediated inflammatory diseases affecting the gastrointestinal tract. Vedolizumab is the first licensed drug in a group of 'gut-selective' biological agents used to treat inflammatory bowel diseases. The GEMINI registrational trials established the efficacy of vedolizumab for the induction and maintenance of remission in both CD and UC, with the most favourable results in tumour necrosis factor (TNF)-antagonist-naive patients. In recent years, a wealth of 'real-world' data has emerged supporting positive clinical, endoscopic and histological outcomes in patients treated with vedolizumab (VDZ) as well as reassuring safety data. More recently, the results of the first head-to-head trials of VDZ and TNF antagonists have been reported, as well as the results of a number of studies exploring the role of therapeutic drug monitoring with VDZ. This review brings together data reported on VDZ to date, including from the GEMINI trials, real-world data and emerging studies regarding therapeutic drug monitoring and immunogenicity. The safety profile of VDZ is also reviewed. Evolving treatment paradigms are explored, including data regarding the role of VDZ in perianal CD, post-operative complications and recurrence, extraintestinal manifestations and pregnancy.